ODAMLARDA TISH EMALINING QATTIQLIGI VA UNI MUSTAHKAMLASH USULLARI - Bakirova Feruza Xasanboy qizi (TADQIQOTLAR, 2026)
Annotation: Enamel is the hardest tissue in the human body and plays a critical role in protecting teeth from mechanical damage, chemical erosion, and bacterial infections. However, enamel can demineralize due to acidic foods, poor oral hygiene, and systemic conditions, leading to increased susceptibility to caries and sensitivity. Recent studies focus on strengthening enamel through remineralization techniques, such as fluoride application, casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) treatments, and the use of bioactive materials in dental care products [1, 2]. Additionally, diet modification, oral hygiene improvement, and preventive dental therapies have shown significant effects on maintaining enamel hardness [3, 4]. Understanding these methods contributes to the prevention of dental diseases and promotes long-term oral health.